Successful 6-Week Antibiotic Treatment for Early Surgical-site Infections in Spinal Surgery. (20th September 2018) - Fernandez-Gerlinger, Marie-Paule; Arvieu, Robin; Lebeaux, David; Rouis, Karama; Guigui, Pierre; Mainardi, Jean-Luc; Bouyer, Benjamin
Abstract: Background: The incidence of spinal surgical site infections (SSIs) remains stable at less than 10%. Surgical reinterventions may be hampered by decubitus, treatment-related adverse events, and cost. In the context of emergence of bacterial resistance, a short duration of antimicrobial treatment is of critical importance. If the duration of treatment for SSI is currently 12 weeks, the aim of our study was to assess the efficacy of an antimicrobial treatment shortened to 6 weeks. Methods: This prospective study was carried out from November 2014 to July 2016 in an 827-bed teaching hospital. After surgical management of SSIs, patients received broad-spectrum antibiotics intravenously for 10 days and orally for the remainder, for a total of 6 weeks. Success was defined as absence of relapse, superinfection, or surgical failure at the end of treatment and at 1-year follow-up. Results: Eighty-five patients were included in this study. The median delay between initial surgery and diagnosis of SSI was 16 days. In 65 cases (76.4%), SSIs were monomicrobial; among these, Staphylococcus aureus was found in 30 cases (46%). Failure was observed in 7 cases (8.2%), with more than half caused by anaerobic bacteria. Conclusions: Surgical management of SSI followed by a 6-week antibiotic treatment is associated with favorable outcome. Anaerobic bacteria seem to play a role in the occurrence of relapses. A 6-week reduction in antibiotic treatment leads to reduction in cost and, likely, also to reduction in the emergence and spread of resistant microorganisms. Abstract : We demonstrate that a 6-week antibiotic treatment is sufficient for early surgical-site infections in spinal surgery. It suggests a benefit of empirical coverage for anaerobic bacteria in surgical procedures such as spinopelvic or extended arthrodesis.